2011
DOI: 10.1177/1359104510378303
|View full text |Cite
|
Sign up to set email alerts
|

Desisting and persisting gender dysphoria after childhood: A qualitative follow-up study

Abstract: The aim of this qualitative study was to obtain a better understanding of the developmental trajectories of persistence and desistence of childhood gender dysphoria and the psychosexual outcome of gender dysphoric children. Twenty five adolescents (M age 15.88, range 14-18), diagnosed with a Gender Identity Disorder (DSM-IV or DSM-IV-TR) in childhood, participated in this study. Data were collected by means of biographical interviews. Adolescents with persisting gender dysphoria (persisters) and those in whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
194
0
35

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 348 publications
(238 citation statements)
references
References 26 publications
9
194
0
35
Order By: Relevance
“…Another factor is whether the feelings of gender dysphoria in children, diagnosed with GID at the time of measurement, will persist into adulthood. Only about 15.8 % of the childhood GID cases will eventually lead to adult GID (Steensma, Biemond, de Boer, & Cohen-Kettenis, 2011). At present, we cannot determine whether the stronger response amplitudes of OAEs in boys with GID may be related to their different gender identity, may be related to current but possibly passing feelings of gender dysphoria and gender variant behaviors, or could be the disposition for a future homosexual orientation.…”
Section: Discussionmentioning
confidence: 89%
“…Another factor is whether the feelings of gender dysphoria in children, diagnosed with GID at the time of measurement, will persist into adulthood. Only about 15.8 % of the childhood GID cases will eventually lead to adult GID (Steensma, Biemond, de Boer, & Cohen-Kettenis, 2011). At present, we cannot determine whether the stronger response amplitudes of OAEs in boys with GID may be related to their different gender identity, may be related to current but possibly passing feelings of gender dysphoria and gender variant behaviors, or could be the disposition for a future homosexual orientation.…”
Section: Discussionmentioning
confidence: 89%
“…However, as the child, and their body, begins to mature, and they start to move outside of the often protective networks of family and primary school, difficulties can start to manifest. Steensma et al (2010) found that the years between 10 and 13 were viewed by young people as the most crucial time in their development for three reasons.…”
Section: Literature Reviewmentioning
confidence: 99%
“…12,15 For others, gender nonconformity may change over the years or disappear altogether. 16 Many children in this latter group explore gender at its margins in a developmental progression toward their later gay identity, at which point the gender nonconformity may dissipate or disappear. 8 For another group, the gender exploration or gender-related stress may emerge in adolescence, often with the onset of puberty as the trigger.…”
Section: Gender Developmentmentioning
confidence: 99%